Addressing the Global Food Security Crisis and Energy Shortages: Innovative Solutions and Policy Interventions for Sustainable Development - Masriadi; Fauziah, Luluk; Gusmailina; Parandy, La Mema; Indaryati (GoAcademica Research & Publishing, 2024)
Food security crises and energy shortages are becoming increasingly pressing global challenges, exacerbated by rapid population growth and inexorable climate change. Land use conflicts, inefficiencies in food and energy systems, and impacts on biodiversity require breakthrough approaches for sustainable solutions. This research aims to investigate innovative solutions and policy interventions that can support sustainable development in overcoming this crisis. The research was conducted through a descriptive qualitative approach, with data obtained from relevant previous studies, and data analysis was carried out to identify patterns and potential solutions. The results of this research find that agricultural and energy policy reform, increased investment in clean technologies, strong international cooperation, and public education and awareness are the keys to achieving food and energy security. Innovations in sustainable agricultural technology and the development of renewable energy have proven vital in reducing dependence on fossil fuels and minimizing environmental impacts. Efficient management of water resources and food and energy systems that operate in a circular model is also important to maximize efficiency and reduce waste. Through the implementation of these strategies, global society can move towards more sustainable development, ensuring access to food and energy for all.